Repetitively burst-spiking neurons in reeler mice show conserved but also highly variable morphological features of layer Vb-fated “thick-tufted” pyramidal cells - Staiger, Jochen F.; Sachkova, Alexandra; Möck, Martin; Guy, Julien; Witte, Mirko (Frontiers in Neuroanatomy, 2022)
Reelin is a large extracellular glycoprotein that is secreted by Cajal-Retzius cells during embryonic development to regulate neuronal migration and cell proliferation but it also seems to regulate ion channel distribution and synaptic vesicle release properties of excitatory neurons well into adulthood. Mouse mutants with a compromised reelin signaling cascade show a highly disorganized neocortex but the basic connectional features of the displaced excitatory principal cells seem to be relatively intact. Very little is known, however, about the intrinsic electrophysiological and morphological properties of individual cells in the reeler cortex. Repetitive burst-spiking (RB) is a unique property of large, thick-tufted pyramidal cells of wild-type layer Vb exclusively, which project to several subcortical targets. In addition, they are known to possess sparse but far-reaching intracortical recurrent collaterals. Here, we compared the electrophysiological properties and morphological features of neurons in the reeler primary somatosensory cortex with those of wild-type controls. Whereas in wild-type mice, RB pyramidal cells were only detected in layer Vb, and the vast majority of reeler RB pyramidal cells were found in the superficial third of the cortical depth. There were no obvious differences in the intrinsic electrophysiological properties and basic morphological features (such as soma size or the number of dendrites) were also well preserved. However, the spatial orientation of the entire dendritic tree was highly variable in the reeler neocortex, whereas it was completely stereotyped in wild-type mice. It seems that basic quantitative features of layer Vb-fated RB pyramidal cells are well conserved in the highly disorganized mutant neocortex, whereas qualitative morphological features vary, possibly to properly orient toward the appropriate input pathways, which are known to show an atypical oblique path through the reeler cortex. The oblique dendritic orientation thus presumably reflects a re-orientation of dendritic input domains toward spatially highly disorganized afferent projections.